Coupled Biphase (1T‐2H)‐MoSe2 on Mold Spore Carbon for Advanced Hydrogen Evolution Reaction. Issue 30 (7th June 2019) - Deng, Shengjue; Ai, Changzhi; Luo, Mi; Liu, Bo; Zhang, Yan; Li, Yahao; Lin, Shiwei; Pan, Guoxiang; Xiong, Qinqin; Liu, Qi; Wang, Xiuli; Xia, Xinhui; et al.
Abstract: Performance breakthrough of MoSe2 ‐based hydrogen evolution reaction (HER) electrocatalysts largely relies on sophisticated phase modulation and judicious innovation on conductive matrix/support. In this work the controllable synthesis of phosphate ion (PO4 3− ) intercalation induced‐MoSe2 (P‐MoSe2 ) nanosheets on N‐doped mold spore carbon (N‐MSC) forming P‐MoSe2 /N‐MSC composite electrocatalysts is realized. Impressively, a novel conductive N‐MSC matrix is constructed by a facile mold fermentation method. Furthermore, the phase of MoSe2 can be modulated by a simple phosphorization strategy to realize the conversion from 2H‐MoSe2 to 1T‐MoSe2 to produce biphase‐coexisted (1T‐2H)‐MoSe2 by PO4 3‐ intercalation (namely, P‐MoSe2 ), confirmed by synchrotron radiation technology and spherical aberration‐corrected TEM (SACTEM). Notably, higher conductivity, lower bandgap and adsorption energy of H + are verified for the P‐MoSe2 /N‐MSC with the help of density functional theory (DFT) calculation. Benefiting from these unique advantages, the P‐MoSe2 /N‐MSC composites show superior HER performance with a low Tafel slope (≈51 mV dec ‐1 ) and overpotential (≈126 mV at 10 mA cm ‐1 ) and excellent electrochemical stability, better than 2H‐MoSe2 /N‐MSC and MoSe2 /carbon nanosphere (MoSe2 /CNS) counterparts. This work demonstrates a new kind of carbon material via biological cultivation, and simultaneously unravels the phase transformation mechanism of MoSe2 by PO4 3‐ intercalation. Abstract : Herein, phosphate ion intercalation induced‐MoSe2 (P‐MoSe2 ) on N‐doped mold spore carbon (N‐MSC) forming P‐MoSe2 /N‐MSC composites as highly efficient HER electrocatalysts are reported. Impressively, a facile phosphorization strategy is adopted to realize phase modulation from 2H‐MoSe2 to 1T‐MoSe2 by PO4 3− intercalation forming biphase coexisted (1T‐2H)‐MoSe2 (namely, P‐MoSe2 ). The designed P‐MoSe2 /N‐MSC composites exhibit extraordinary HER performance.